2017
DOI: 10.1111/bjh.14489
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the NCCNIPI for diffuse large B‐cell lymphoma (DLBCL): the addition of β2‐microglobulin yields a more accurate GELTAMOIPI

Abstract: The study included 1848 diffuse large B-cell lymphoma (DLBCL)patients treated with chemotherapy/rituximab. The aims were to validate the National Comprehensive Cancer Network International Prognostic Index (NCCN-IPI) and explore the effect of adding high Beta-2 microglobulin (β2M), primary extranodal presentation and intense treatment to the NCCN-IPI variables in order to develop an improved index. Comparing survival curves, NCCN-IPI discriminated better than IPI, separating four risk groups with 5-year overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 29 publications
4
76
1
1
Order By: Relevance
“…With the new model, the highest‐risk group had five‐year PFS of 19% and five‐year OS of 24%, favourable compared with IPI (45% and 59%, respectively). Likewise, a better high‐risk assessment of the new score was observed when compared to previously reported scores such as Tumor Score (TS), NCCN‐IPI and GELTAMO‐IPI (Rodriguez et al ., ; Zhou et al ., ; Montalbán et al ., ), which showed higher five‐year PFS and five‐year OS (32%, 38%, 29% and 45%, 46%, 40% respectively).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…With the new model, the highest‐risk group had five‐year PFS of 19% and five‐year OS of 24%, favourable compared with IPI (45% and 59%, respectively). Likewise, a better high‐risk assessment of the new score was observed when compared to previously reported scores such as Tumor Score (TS), NCCN‐IPI and GELTAMO‐IPI (Rodriguez et al ., ; Zhou et al ., ; Montalbán et al ., ), which showed higher five‐year PFS and five‐year OS (32%, 38%, 29% and 45%, 46%, 40% respectively).…”
Section: Resultsmentioning
confidence: 96%
“…The NCCN‐IPI, compared with the IPI, incorporates age and LDH, achieving an enhanced capacity to discriminate low‐ and high‐risk groups (Zhou et al ., ; El‐Galaly et al ., ). With the same aim, our group recently reported the GELTAMO‐IPI, including all variables of IPI, with a further categorization of age and ECOG‐PS, as well as B2M (Montalbán et al ., ). In 1992, the MD Anderson Cancer Centre reported the TS exclusively considering variables related to the tumour: high LDH, Ann Arbor stage III/IV, high B2M, bulky mass and the presence of B symptoms (Rodriguez et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The enhanced IPI (which improved on the specification of age and lactate dehydrogenase [LDH] as non-binary variables) has identified involvement of CNS, liver/gastrointestinal (GI) tract, lung, or marrow as additional unfavorable prognostic factors [9]. The Spanish Lymphoma Study Group evaluated extranodal origin in addition to the IPI, and found no additive prognostic value, but specific anatomic sites were not distinguished [13]. In contrast, a Danish-Canadian series of 443 patients staged with positron emission tomography (PET) found that 67% had extranodal involvement, that PET uptake in bone/bone marrow, pleura, or female reproductive organs was independently associated with worse progression-free survival (PFS) and OS, and that >2 or >3 involved sites conferred progressively worse prognosis [3].…”
Section: Assessment Of Prognosis In Dlbclmentioning
confidence: 99%
“…Further independent studies are required to validate the proposed greater effectiveness of newer indices, including the National Comprehensive Cancer Network (NCCN)-IPI and GELTAMO-IPI [16, 17]. The inclusion of biomarkers and genes implicated in the biology of DLBCL has not significantly improved the prognostic accuracy of the IPI [18, 19].…”
Section: Staging and Risk Assessmentmentioning
confidence: 99%